Фенотиповий профіль лімфоцитів периферичної крові у хворих на рак щитоподібної залози у ранні терміни після радіойодтерапії - Замотаєва, Г. А.; Степура, Н. М. (Clinical Endocrinology and Endocrine Surgery, 2008)
The authors have carried out a study of the phenotype of peripheral blood lymphocytes in 26 patients with differentiated form of thyroid cancer in early terms (6 days) after administration of therapeutic doses of radioiodine (4130-4730 MBq). The results were compared with baseline indicators in patients before radioiodine therapy, and in donors. Significant changes have been revealed in blood lymphocyte phenotype in one week after I-131 administration: a decrease in CD19+, CD3+ content and activated HLA-DR+-cells, an unbalance of T-lymphocyte subpopulations, an increase in the number of cells expressing CD95. Further immunological monitoring of patients receiving radioiodine therapy is needed for an estimation of immuno-hematological after-effects of radioiodine, for determining their degree and duration.